2000
DOI: 10.1182/blood.v95.6.1925
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of 13q14 remains an independent adverse prognostic variable in multiple myeloma despite its frequent detection by interphase fluorescence in situ hybridization

Abstract: Interphase fluorescence in situ hybridization (FISH) studies of chromosomal region 13q14 were performed to investigate the incidence and clinical importance of deletions in multiple myeloma (MM). Monoallelic deletions of the retinoblastoma-1 (rb-1) gene and the D13S319 locus were observed in 48 of 104 patients (46.2%) and in 28 of 72 (38.9%) patients, respectively, with newly diagnosed MM. FISH studies found that 13q14 was deleted in all 17 patients with karyotypic evidence of monosomy 13 or deletion of 13q bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
124
2
12

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(150 citation statements)
references
References 26 publications
12
124
2
12
Order By: Relevance
“…Therefore, there is evidence to support that the cell cycle regulatory pathways, in which the Rb, cyclin D and p16 are involved, may play a central role in the pathogenesis of MM. In line with these observations, a poor prognosis has been reported for patients with Rb deletions (Pérez-Simon et al, 1998;Zojer et al, 2000), )13/13q deletions (Tricot et al, 1995;Seong et al, 1998), and now p16 methylation, while an increased number of copies of the p16 gene, as reflected by the existence of trisomy 9, has been related to a better clinical outcome among MM patients (Pérez-Simon et al, 1998).…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, there is evidence to support that the cell cycle regulatory pathways, in which the Rb, cyclin D and p16 are involved, may play a central role in the pathogenesis of MM. In line with these observations, a poor prognosis has been reported for patients with Rb deletions (Pérez-Simon et al, 1998;Zojer et al, 2000), )13/13q deletions (Tricot et al, 1995;Seong et al, 1998), and now p16 methylation, while an increased number of copies of the p16 gene, as reflected by the existence of trisomy 9, has been related to a better clinical outcome among MM patients (Pérez-Simon et al, 1998).…”
Section: Discussionmentioning
confidence: 52%
“…Our data would argue that, in addition to the more traditional prognostic markers, such as B2M, albumin and haemoglobin levels, a prognostic system to identify patients that would benefit most from novel therapies should incorporate treatment response, given that many patients destined to relapse early after the first high dose cannot always be identified at presentation using the traditional markers. Although cytogenetical data was not assessed in this study, several publications have demonstrated the adverse prognostic impact of chromosome 13 abnormalities, particularly deletion of 13q14, which would be an additive factor in risk stratification (Tricot et al, 1997;Zojer et al, 2000;Facon et al, 2001;Kaufmann et al, 2003;Shaughnessy et al, 2003). A temporal profile could therefore be established, enabling subgroups of patients to be streamlined according to their perceived risk of relapse at each time point along a standard protocol.…”
Section: Discussionmentioning
confidence: 99%
“…In multiple myeloma (MM), partial or complete deletion of chromosome 13q [del(13q)] represents one of the most important parameters predicting for short survival after both standard-dose and high-dose chemotherapy (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). The adverse prognostic implication of a del(13q) was initially observed in investigations by metaphase cytogenetics (2)(3)(4)(5) and subsequently by interphase fluorescence in situ hybridization (FISH) studies (6)(7)(8)(9)(10), although a del(13q) was more frequently observed by FISH than by metaphase cytogenetics. However, it has remained unclear whether or not del(13q) as detected by FISH only would provide the same prognostic information as its detection by metaphase cytogenetics (11).…”
mentioning
confidence: 99%